Pembelajaran Aktif Melalui Metode Imla’ untuk Meningkatkan Kemampuan Menulis Huruf Arab pada Siswa Kelas VIIA SMPN 2 Tulakan Kecamatan Tulakan Kabupaten Pacitan Semester Ganjil Tahun Pelajaran 2018/ 2019 - Abdulloh Sadjad (LP2M Sekolah Tinggi Agama Islam Nahdlatul Ulama Pacitan, 2019)
In the development of science today is supposed to be the method of teaching reading adapted to the context and the use of acceptable language students, not giving words - words without context and meaning. Likewise, teaching writing, writing skills (hand writing) with the copy, imitate, and so is the way it - it (Godman and his friends: 1986). Teaching literacy is not only learning rang and wrote letters by stringing-rangkainya but an attempt to develop the literacy skills (reading and writing) that is based upon the ability to speak. So that the child's cognitive ability in using the language would be better.Â Â Â Â Â Â Â Â Â Â Â Â Â Â In Religion Islamic learning in primary school / madrasah rely heavily on the use of methods that attractive and interesting. Learning that a draw would entice children to keep and bear studying Islamic religion as a 2nd language after their mother tongue. If students are interested in learning it will easily improve student achievement in language. In some students, learning Islamic religion is very boring because they already feel able and delivery of material that is less attractive thus indirectly becoming weaker students in the arrest of the material. Writers as a teacher of Religion Islam strongly felt problem that occurred during this study.